2002
DOI: 10.1253/circj.66.145
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Quality of Cardiovascular Surgery Care Using Risk Stratification Analysis According to the EuroSCORE Additive Model

Abstract: or an evaluation of the results of cardiovascular surgery, crude operative mortality rate (ie, the number of deaths divided by the number of operations) is generally employed, although these raw outcome data do not reflect the preoperative condition of the individual patient. Therefore, to resolve that problem, risk stratification analysis was developed 1-3 for 2 major uses: one is estimating the risk of surgical mortality faced by an individual patient, as an aid to patients and physicians contemplating cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 11 publications
(16 reference statements)
2
26
0
2
Order By: Relevance
“…Mean patients` age in the study was similar to results of other investigators [3][4][5][6][7][8][9]14]. Our patients had multiple risk factors, with higher frequency compared to some other investigated groups [8].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Mean patients` age in the study was similar to results of other investigators [3][4][5][6][7][8][9]14]. Our patients had multiple risk factors, with higher frequency compared to some other investigated groups [8].…”
Section: Discussionsupporting
confidence: 88%
“…Prior non-recent (MI) and its anteroseptal localization were important predictors of increased 5-yr mortality. Recent MI (less than 90 days prior to CABG) was determined as the predictor of increased perioperative mortality in EuroSCORE risk system prediction [1][2][3][4][5][6][7]17]. This study showed that even non-recent myocardial infarction was related to increased 5-yr mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EuroSCORE'un standart ya da additif sistem olarak bilinen ilk versiyonu belirlenen faktörlerin lojistik regresyon metoduyla elde edilen risk katsayılarının doğrudan toplanması esasına dayanmaktadır. Sistemin belirleyicilik gücü birçok merkezin sonuçlarında mükemmele yakın iken ilerleyen yıllarda yüksek risk grubunda yetersiz kaldığı gündeme getirilmeye başlanmıştır (3)(4)(5)(6). Nashef ve ark.…”
Section: Introductionunclassified
“…3 Because of its simplicity in regard to evaluating the operative risk for individual patients, the EuroS-CORE, especially the logistic EuroSCORE, 4 has been widely used to predict mortality associated with cardiac surgery not only in European countries but also in Japan. [5][6][7][8] However, the limitation of the STS National Database and the EuroSCORE is that these algorithms have not been established for Japanese patients. Thus, JapanSCORE was developed with the aim of establishing a Japanese original risk prediction model.…”
Section: Risk Prediction Of Cardiovascular Surgery In Japanese Patienmentioning
confidence: 99%